(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
Historically, literature is one of the oldest arts that emerged from the original syncretic art along with music and dance. In this way, it has become one of the most widespread arts that humans come into contact with from an early age, and its significance for human mental development is multifaceted. The significance of literature for students is immense and multifaceted. The significance of literature for students is enormous and multifaceted. With the help of reading, they free themselves from everyday obligations and pressures and plunge into another world – the world of fiction, live the lives of the characters, think about their problems, problematically examine their actions and draw their own personal conclusions regarding them. The study of a work of art in school is not only a process of experiencing the artistic text, but also a means of developing the thinking, feelings and aesthetic taste of students. The goal is not only to understand the content, but also to analyze the artistic means, composition and ideas of the work. The study of is a complex educational process in which the student matures as a person. Literature teaching plays a key role in the development of students’ cognitive abilities. When we talk about cognition, we mean a group of mental processes that are created in the human brain, such as: attention, memory, creation and understanding of language, learning, reasoning, problem solving and adopting a personal attitude. Cognitive abilities are complex mental processes that enable students to perceive and process information and at the same time to think logically and critically using language and symbols. In this way, literature develops: linguistic understanding, critical thinking, memory, creativity, empathy and social awareness.